2022
DOI: 10.1155/2022/8242164
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Different Passing Methods of Physical Fitness in Football Using Deep Learning

Abstract: Deep learning is a new direction in the field of machine learning, which learns the inherent laws and levels of data sample representation. The information gained during learning plays an important role in interpreting data such as text, images, and speech. This paper aims to study how to analyze and study the physical energy consumption of passers and receivers in different passing methods in football based on deep learning. This paper proposes the problem of physical energy consumption, which is based on dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…NetworkX is a network modelling tool developed based on the python platform. Its connotative network analysis method can provide users with network analysis and modelling of building planes [27][28][29]. NetworkX includes storing image classes, creating image classes, and implementing image drawing functions through the Graphviz [18] tool library.…”
Section: Resultsmentioning
confidence: 99%
“…NetworkX is a network modelling tool developed based on the python platform. Its connotative network analysis method can provide users with network analysis and modelling of building planes [27][28][29]. NetworkX includes storing image classes, creating image classes, and implementing image drawing functions through the Graphviz [18] tool library.…”
Section: Resultsmentioning
confidence: 99%
“…Dengan adanya media di harapkan membantu dalam proses pembelajaran siswa melalui penggunaan media dinding, siswa diharapkan lebih mudah mengembangkan teknik dasar passing dalam permainan sepak bola. Selain itu diharapkan siswa juga bisa lebih memahami semua teknik dasar dan gerak untuk memposisikan tubuh dalam permainan sepak bola dengan cara melakukan permainan sepak bola menggunakan media dinding (Mclean, 2019;Phatak, 2019;Pollard, 2019;Wang, 2022). Menurut (Mahmudah, 2018) media pembelajaran adalah sarana non personal (bukan manusia) yang di gunakan oleh guru sebagai pemegang peranan dalam proses belajar mengajar untuk mencapai tujuan.…”
Section: Pendahuluanunclassified
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%